Expected Role of the Community in Decision-Making for the Development of Sanankerto Tourism Village, Turen Sub-District, Malang District - Widhiani, Sabilla Kurnia; Dinanti, Dian; Leliana, Defin Helda; Fauzi, Isnan; Rachman, Cyril Bernard; Habunga, Mostan (Perencanaan Wilayah dan Kota FT UB, 2024)
Sanankerto Tourism Village was recognized as one of the best tourism villages at the 2021 Anugerah Desa Wisata Indonesia award. However, the Covid-19 pandemic led to significant challenges, causing many tourism products and activities to falter. There is now a discourse on revitalizing Sanankerto Tourism Village, highlighting the need to assess the community's willingness to engage in decision-making processes regarding the village's development. Community involvement is crucial to ensure that grassroots ideas, which are vital for development, are incorporated. Engaging the community in the development process is expected to make Sanankerto Tourism Village more advanced, innovative, and creative, while also fostering a sense of ownership and responsibility among the residents. The level of community participation was evaluated using descriptive analysis, scoring, and weighting methods to determine its value. The analysis revealed a score of 1,213.10, placing the community in the Delegated Power category on Arnstein's Ladder of Participation. At this level, the government grants authority to the community for making planning decisions, giving them control over some or all of the programs to be implemented.